Longer-term effects of the Pantawid Pamilyang Pilipino program: Evidence from a randomized control trial cohort analysis: (Third wave impact evaluation) - Aniceto C. Orbeta; Kris Ann M. Melad; Nina Victoria V. Araos (Philippine Institute for Development Studies (PIDS), 2021)
This study was conducted as part of the 3rd wave impact evaluation of the Pantawid Pamilyang Pilipino program. The objective is to analyze the longer-term "lock-in" effects of time-critical program inputs on education and health outcomes for specific cohorts of beneficiaries. The cohorts are known to benefit more from inputs received at critical points in their first 1000 days of life and from age-appropriate start of schooling. The data, collected from November to December 2017, covered 2,265 households with children born between April 2009 and April 2013 from the original treatment and control barangays of the first impact evaluation of the program that used Randomized Control Trial (RCT) design. The sampling was designed to take advantage of the phased implementation and capture children born within the period when there was asymmetry in program participation and receipt of benefits between treatment and control areas. Children and mothers in the original treatment areas are presumed to have received program benefits during the critical period while children and mothers in the control areas are presumed to have received benefits beyond the critical period. The findings show that timely exposure to Pantawid Pamilya inputs during the first 1000 days of life result in lower prevalence of severe underweight, prevalence of illness with diarrhea, and fever among children. Positive program impact was observed for age of start of schooling in first grade (grade 1) and cumulative number of years of delay in schooling, but these results were not consistently observed in other estimations that control for confounding variables. The small impact of the program in level progression in primary school suggest that the control group were able to catch-up with their counterparts in the treatment group. In general, results of the study highlight the importance of providing program inputs together with a comprehensive package of supplementary interventions during the first 1000 days of life to achieve significant results in health and nutrition outcomes of children. Misconceptions on the start of schooling must also be addressed to ensure that children start school on time and avoid delays in progression through grade levels.
Keywords: 330; Pantawid Pamilya; Cash transfers; RCT; Cohort; lock-in effects; health; nutrition